2013
DOI: 10.1186/1471-2334-13-270
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological profile and surgical treatment of abdominal tuberculosis: a single centre experience in northwestern Tanzania

Abstract: BackgroundAbdominal tuberculosis continues to be a major public health problem worldwide and poses diagnostic and therapeutic challenges to general surgeons practicing in resource-limited countries. This study was conducted to describe the clinicopathological profile and outcome of surgical treatment of abdominal tuberculosis in our setting and compare with what is described in literature.MethodsA prospective descriptive study of patients who presented with abdominal tuberculosis was conducted at Bugando Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
48
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 23 publications
14
48
3
1
Order By: Relevance
“…Most of the other studies have also shown similar observations. [8][9][10] In present study cases with primary abdominal tuberculosis (68%) were more common than patient with abdominal tuberculosis associated with pulmonary TB on family history of pulmonary TB (32%).…”
Section: 14mentioning
confidence: 85%
See 4 more Smart Citations
“…Most of the other studies have also shown similar observations. [8][9][10] In present study cases with primary abdominal tuberculosis (68%) were more common than patient with abdominal tuberculosis associated with pulmonary TB on family history of pulmonary TB (32%).…”
Section: 14mentioning
confidence: 85%
“…Male:female ratio was (1.4:1), in study by Urabinohatti KA ratio was 1.8:1, Awasthi S also reported ratio of 1.4:1, and male preponderance was the finding in most of the studies. [10][11][12] However in some studies Sankpal J et al Male:female ratio was 1:1.6, Hossain SM reported ratio of 5:8.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations